Животные и «звери» в произведениях Мартина Макдонаха - Кириченко, Д.А. (Культура народов Причерноморья, 2014)
Проводится подробное исследование образов животных в текстах Мартина Макдонаха.
Значимость данных персонажей в работах автора является характерной не для какого-то конкретного
текста, а выступает одной из художественных особенностей его драматургии. На основе событий,
связанных с животными, писатель задумывается об актуальной проблеме нашего времени: почему
проявляя искренние и заботливые чувства к животным, человек жестоко убивает себе подобных. Проводиться докладне дослідження образів тварин у текстах Мартіна Макдонаха.
Значимість даних персонажів у роботах автора є характерною не для якогось конкретного тексту, а
виступає однією з художніх особливостей його драматургії. На основі подій, пов'язаних з тваринами,
письменник замислюється про актуальну проблему сьогодення: чому проявляючи щирі й турботливі
почуття до тварин, людина жорстоко вбиває собі подібних. The article gives a detailed analysis of the images of animals in the plays «The Lieutenant of
Inishmore», «The Beauty Queen of Leenane», «The Lonesome West», «The Cripple of Inishmaan», «A Skull in
Connemara» and «The Pillowman» by Martin McDonagh. Different events related to animals are typical not
only for his plays but also for his films. The question about the importance of these characters can be found only
in the evaluation of the foreign literature criticism in the articles by Patrick Burke and Patrick Lonergan.
However, these essays only refer us to the most famous examples of literature and cinema in which some scenes
of violence and cruelty to animals are present. The significance of these characters in the works of the author is
not characteristic for a particular text, and represents one of his drama's artistic features. On the basis of
animal-related events, the writer thinks about the actual problem of our time: why showing sincere and caring
feelings to animals, man brutally kills other people. The indicative love for animals is manifested by some
characters only to a certain kind of animals, while to the others they act in a bad way.